Implementation of Android-Based Interactive Learning Media on Students' Critical Thinking Skills in Physics Learning - Rahmawati, Silpia; Warliani, Resti; Mulvia, Rahmadhani (Lensa: Jurnal Kependidikan Fisika, 2025)
This study aims to determine the average improvement in high school students' critical thinking skills in physics learning by using Android-based interactive learning media. This research is quantitative in nature and employs a quasi-experimental pretest-posttest control group design. The research population consisted of all grade XI students at one school in the Garut District during the even semester of the 2024/2025 academic year. The study involved two classes: XI-J (the experimental group, n = 34 students) using Android-based learning media, and XI-I (the control group, n = 34 students) using Google Sites. The research instruments included student response questionnaires and pretest-posttest questions based on the critical thinking aspects defined by Ennis. Data were analyzed using tests for homogeneity, normality, a t-test, and the N-gain test, with the aid of SPSS. The questionnaire results showed an 81.24% acceptance level for the Android-based media, categorized as very good, while observations indicated that the implementation of the learning process reached an average of 90%. Pretest-posttest analysis revealed a significant improvement in students' critical thinking skills. The experimental groupâ€™s average score increased to 77.74 (categorized as good), while the control group achieved 65.59 (categorized as sufficient). The t-test yielded a significance value of 0.01 < 0.05; hence, Hâ‚€ was rejected and Hâ‚ was accepted, confirming a significant difference between the two groups. Based on these results, it can be concluded that the use of Android-based interactive media is proven to be more effective in improving students' critical thinking skills in the topic of static fluids compared to the use of Google Sites.